DIAGNÓSTICO DE LOS SISTEMAS SOCIOCULTURAL Y ECONÓMICO, PROPUESTA Y MODELO DE GESTIÓN PARA EL PLAN DE DESARROLLO Y ORDENAMIENTO TERRITORIAL DE LA PARROQUIA CHAQUINAL, CANTÓN PINDAL, PROVINCIA DE LOJA, 2015 - Veintimilla Mendoza, Marycruz (2016)
The Plan of Develop and Territory Ordering active in Chaquinal parish lacks of actualized information for the approach of action proposed according to the population requirements. For that reason, this investigation has like general objective: contribute to the develop, through action proposed to improve de life conditions of its habitants. Foe which, it was used the methodology proposed by SENPLADES and information collected through surveys and participatory assemblies performed on a sample of 153 people from 9 neighborhoods from the Chaquinal parish; those instruments allowed to develop the general diagnostic in the socio-cultural and economic field from the parish, visualizing the demographic indicators and action lines like education, health, basic services, productivity, and others. Reaching the conclusion, that the population form Chaquinal lacks of potable water and sewage system necessaries to get a worthy life. In addition, in the agriculture, presence of plagues and flooding provoke big crop loss; therefore, the Decentralized self-government must make the pertinent efforts to carry out the projects proposed, focused on satisfy the basic necessities and raise the productive level. KEYWORDS: Planning/ territory/ Plan od Develop and Territory Ordering/Chaquinal